Mental freedom: Who has control-the rider or the horse? - Wiesner, Jane L. (International journal of Dharma Studies, 2014)
This paper has been reproduced and modified from a PhD dissertation (Deakin University, 2013) written by the author titled Freedom and Conditionality: Analysing Mental and Yogic Models of Freedom'. It is a cross-cultural, crossdisciplined work based on an exploration into Eastern and Western concepts of mental freedom.